Arctigenin Treatment Protects against Brain Damage through an Anti-Inflammatory and Anti-Apoptotic Mechanism after Needle Insertion - Song, Jie; Li, Na; Xia, Yang; Gao, Zhong; Zou, Sa-feng; Kong, Liang; Yao, Ying-Jia; Jiao, Ya-Nan; Yan, Yu-Hui; Li, Shao-Heng; Tao, Zhen-Yu; Lian, Guan; et al. (Frontiers in Pharmacology, 2016)
Convection enhanced delivery (CED) infuses drugs directly into brain tissue. Needle insertion is required and results in a stab wound injury (SWI). Subsequent secondary injury involves the release of inflammatory and apoptotic cytokines, which have dramatic consequences on the integrity of damaged tissue, leading to the evolution of a pericontusional-damaged area minutes to days after in the initial injury. The present study investigated the capacity for arctigenin (ARC) to prevent secondary brain injury and the determination of the underlying mechanism of action in a mouse model of SWI that mimics the process of CED. After CED, mice received a gavage of ARC from 30 min to 14 days. Neurological severity scores (NSS) and wound closure degree were assessed after the injury. Histological analysis and immunocytochemistry were used to evaluate the extent of brain damage and neuroinflammation. Terminal deoxynucleotidyl transferase dUTP nick end labeling (TUNEL) was used to detect universal apoptosis. Enzyme-linked immunosorbent assays (ELISA) was used to test the inflammatory cytokines (tumor necrosis factor (TNF)-α, interleukin (IL)-6 and IL-10) and lactate dehydrogenase (LDH) content. Gene levels of inflammation (TNF-α, IL-6 and IL-10) and apoptosis (Caspase-3, Bax and Bcl-2) were detected by reverse transcription-polymerase chain reaction (RT-PCR). Using these, we analyzed ARC’s efficacy and mechanism of action. Results: ARC treatment improved neurological function by reducing brain water content and hematoma and accelerating wound closure relative to untreated mice. ARC treatment reduced the levels of TNF-α and IL-6 and the number of allograft inflammatory factor (IBA)- and myeloperoxidase (MPO)-positive cells and increased the levels of IL-10. ARC-treated mice had fewer TUNEL+ apoptotic neurons and activated caspase-3-positive neurons surrounding the lesion than controls, indicating increased neuronal survival. Conclusions: ARC treatment confers neuroprotection of brain tissue through anti-inflammatory and anti-apoptotic effects in a mouse model of SWI. These results suggest a new strategy for promoting neuronal survival and function after CED to improve long-term patient outcome.